2021
DOI: 10.1186/s13030-021-00210-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations between lifestyle behaviour changes and the optimal well-being of middle-aged Japanese individuals

Abstract: Background Psychological well-being has been associated with reduced mortality rates in both healthy and diseased populations. However, there is considerably less evidence on the effect of lifestyle behaviours on positive health outcomes such as well-being. This study examines the association between lifestyle behaviours and optimal well-being. Methods From a total of 4324 Japanese individuals who participated in an annual health check-up in 2017, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Convergence with the current study findings was also observed by Takao et al (2021). They found a strong association between higher well-being and over 30 minutes of intensive exercise more than twice a week and over one-hour walking every day.…”
Section: Discussionsupporting
confidence: 90%
“…Convergence with the current study findings was also observed by Takao et al (2021). They found a strong association between higher well-being and over 30 minutes of intensive exercise more than twice a week and over one-hour walking every day.…”
Section: Discussionsupporting
confidence: 90%
“…Regular exercise lasting over one year appears to be a key behavior to meet the recommended level of physical activity. Regularly engaging in physical activities is associated with perceived good health, including mental health [ 9 , 28 , 29 , 30 ]. A systematic review examining the interrelationship between sleep and exercise concluded that exercise improved sleep quality; however, no difference and a negative impact of exercise on sleep were observed [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, in Tonga, health care is free for all citizens [15] and could be the reason why Tongan people do not include health insurance in their budget. In previous studies, having health insurance had positive impacts on health outcomes and the frequency of visits to health care providers [30][31][32][33][34][35]. Thus, it could be a contributing factor for Tongan adults not having regular health check-ups because of a lack of health insurance scheme, but further research and exploration are needed.…”
Section: Discussionmentioning
confidence: 94%
“…Three main recommendations from this study, firstly is the promotion and advocation of regular health check-ups. As shown in studies in other countries like Japan [ 31 ], China [ 36 ], and Vietnam [ 37 ], people who have had regular health check-ups have earlier detection and better management of hypertension. Secondly, government and ministry of health Tonga should empower and streamline regular health check-up [ 25 27 ] process and sharing of information is recommended to enhance continuity of health care [ 28 , 29 , 33 36 ].…”
Section: Discussionmentioning
confidence: 99%